2022
DOI: 10.3389/fonc.2022.958128
|View full text |Cite
|
Sign up to set email alerts
|

Does the shape of the electric pulse matter in electroporation?

Abstract: Electric pulses are widely used in biology, medicine, industry, and food processing. Numerous studies indicate that electroporation (EP) is a pulse-dependent process, and the electric pulse shape and duration strongly determine permeabilization efficacy. EP protocols are precisely planned in terms of the size and charge of the molecules, which will be delivered to the cell. In reversible and irreversible EP applications, rectangular or sine, polar or bipolar pulses are commonly used. The usage of pulses of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 132 publications
1
15
0
Order By: Relevance
“…This was hypothesized to arise from the higher displacement currents associated with a faster rising electric pulse. Other reports also indicate similar pulse-dependent biooutcomes 105 . Our prior modeling established that nanosecond excitation could rapidly induce large TMPs in the mitochondrion 47 .…”
Section: Resultsmentioning
confidence: 65%
“…This was hypothesized to arise from the higher displacement currents associated with a faster rising electric pulse. Other reports also indicate similar pulse-dependent biooutcomes 105 . Our prior modeling established that nanosecond excitation could rapidly induce large TMPs in the mitochondrion 47 .…”
Section: Resultsmentioning
confidence: 65%
“…Studies on the clinical application of IRE techniques have reported that the possibility of ventricular or atrial fibrillation and muscle contraction must be monitored carefully when high voltages are used during treatment owing to the possibility of additional undesirable consequences such as pain [19][20][21][22]. Thus, studies have been conducted to address these problems, including increasing the frequency with a nano-second level PW (H-FIRE) [19,20,24,28], applying a bipolar rectangular pulse [19,44], and optimizing the IRE electrode configuration, considering its shape and material [25,26]. However, these methods resulted in smaller ablation areas than conventional IRE owing to bipolar cancellation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the variability in the treatment effect was high, the system was complex, and the risk of using high voltage was also inherent. Recently, with the development of highvoltage power semiconductor technologies and parts while simplifying the configuration of the systems, these treatments have become safe for the human body, and it is possible to generate various electric pulses, and thus, studies are carrying out new pulse shapes [44]. In this paper, a study was conducted on whether the voltage required for ablation could be lowered when an exponential decay waveform was consecutively applied after applying an IRE using only several square pulses, which have been traditionally used.…”
Section: Discussionmentioning
confidence: 99%
“…To achieve electroporation, a transmembrane voltage of at least 0.2 V is required, typically ranging from 0.5 to 1 V [49]. The effectiveness of electroporation is highly influenced by various operational parameters such as pulse duration, number of pulses, and magnitude of the voltage [50,51].…”
Section: Traditional Electroporationmentioning
confidence: 99%